Pemberdayaan Kelompok Masyarakat Pengawas (POKMAKWAS) melalui Pelatihan Restocking Ikan Nilem untuk Mendukung Pelestarian Ikan Endemik di Desa Negarajati, Kabupaten Cilacap - Sukardi, Purnama; Anjaini, Jefri; Baruna Kusuma; Asro Nurhabib; Lilik Setiyaningsih; Frentina Murti Sujadi; Rose Dewi; Arif Yulianto (Universitas Mataram, 2025)
The Nilem fish (Osteochilus hasselti), an indigenous freshwater species in Indonesia, has experienced a significant population decline due to various factors including habitat degradation from land conversion, water pollution, and overfishing. This decline threatens the stability of local aquatic ecosystems and biodiversity. To address this critical issue, a Restocking program was implemented in Negarajati Village, Cilacap Regency, specifically targeting the restoration of the Nilem fish population and the improvement of damaged aquatic ecosystems. The program adopted an integrated approach emphasizing active community involvement, particularly through the empowerment of Community Supervisory Groups (POKMAKWAS). Training provided to POKMAKWAS encompassed crucial aspects such as Nilem fish restocking techniques, water quality monitoring, sustainable natural resource management, waste management, and eco-friendly aquaculture. The methodology included local breeding and seed procurement (16,000 Nilem fish measuring 8-9 cm were stocked), periodic stocking at appropriate times and locations, continuous environmental supervision and monitoring, and robust community engagement. Academics from the Faculty of Fisheries and Marine Sciences, Universitas Jenderal Soedirman (FPIK UNSOED), facilitated and provided technical and scientific knowledge. The Restocking initiative aims to ensure the optimal growth and development of the stocked fish, fulfilling local fish resource needs, and supporting regional food security. The empowerment of POKMAKWAS is crucial as it fosters community understanding of endemic fish conservation rules and ecosystem sustainability, enabling them to act as effective supervisory agents against habitat destruction. This program is expected to become a routine, sustainable activity for POKMAKWAS, with continuous monitoring and evaluation by the local Fisheries Department and government support. The success of this program could lead to the expansion of stocking points and significantly increase community awareness regarding the importance of managing endemic fish and aquatic ecosystems sustainably. This collaborative effort between the community, government, and academia holds potential for positive economic impacts on local fishermen and serves as a model for endemic fish conservation in other regions.